(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2018)
this sector, called non-additive fuels or simple fuels. A survey was made of laws that influence this sector and were considered relevant to the study, following a theoretical review focused on consumer buying processes and the factors that influence these choices. A questionnaire was also applied to fuel consumers, obtaining a sample of 327 consumers, in order to know people’s opinions about the fuel market and its products. In this way, consumers would be able to acquire more and better information, enabling them to make the best possible choices when they want to buy fuel.